PENGARUH FAKTOR LINGKUNGAN BISNIS EKSTERNAL DAN PERENCANAAN STRATEGIK TERHADAP KINERJA PERUSAHAAN - Andri Ariansyah Nasution; Anggi Mayasari Lubis; Dini Azlina Pane; Sherlyta Mardiani (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This study aims to determine the influence of external business environmental factors and strategic planning on company performance. This study was conducted with a sample of 30 respondents with this sampling technique is probability sampling from multiple linear regression calculations, obtained Y = 3.302 + 0.564X1 + 0.661X2 The results of this study obtained t test, for variables: External Business Environment Factors (X1) t count (2.505) > t table (2.051831) with a significant value of 0.000 <0.05, meaning that there is a significant influence of External Business Environmental Factors on Company Performance. Meanwhile, for the results of the t-test of Strategic Planning (X2), namely t count (2.690) > t table (2.051831) with a significant level of 0.000 <0.05, meaning that there is a significant effect of Strategic Planning on Company Performance. Based on the calculated F test of 36,489 > Ftable 3.35, which means that simultaneously or together External Business Environmental Factors (X1) and Strategic Planning (X2) have a significant effect on Company Performance.